Hydrophobic and hydrophilic balance and its effect on mesophase behaviour in hydroxyalkyl ethers of methyl glucopyranoside - Singh, Madan K.; Xu, Rui; Moebs, Sylvie; Kumar, Anil; Queneau, Yves; Cowling, Stephen J.; Goodby, John W. (Chemistry-A European Journal, 2013)
Four series of monosubstituted methyl -D-glucopyranoside hydroxyalkyl ethers were prepared and their thermotropic and lyotropic self-organising properties were investigated in terms of the hydrophobichydrophilic balance with respect to their molecular structures. The results obtained lead us to a new understanding of the forces that drive the formation of condensed soft-matter phases.
Keywords: carbohydrates; liquid crystals; mesophases; Self-assembly; soft matter